Status and conservation of the snow leopard Panthera uncia in Api Nampa Conservation Area, Nepal. Issue 3 (30th May 2020) - Khanal, Gopal; Poudyal, Laxman Prasad; Devkota, Bishnu Prasad; Ranabhat, Rishi; Wegge, Per
Abstract: The snow leopard Panthera uncia is globally threatened and reliable information on its abundance, distribution and prey species is a prerequisite for its conservation. In October–November 2014 we assessed the distribution of the snow leopard in the recently established Api Nampa Conservation Area in the Nepal Himalayas. Within selected blocks we conducted sign surveys and counted the number of bharal Pseudois nayaur, its principal wild prey, along transects totalling 106 km. We recorded 203 putative snow leopard signs at an encounter rate of 1.91 signs/km. Generalized linear models of the number of signs detected per transect showed that elevation had a positive influence and human activities a negative influence on sign encounter rate; prey abundance had only a weak positive influence on sign encounter rate. Within the effectively surveyed area of c. 200 km 2, we counted 527 bharal at an estimated density of 2.28 animals/km 2 . Recruitment of bharal was low, estimated at 48 kids/100 adult females, most likely a result of poor or overgrazed rangeland. We estimate the total number of bharal in this conservation area to be > 1, 000, a prey base that could sustain 6–9 snow leopards. Based on our field observations, we identified human disturbance and habitat degradation associated with extraction of non-timber forest products, livestock grazing, and poaching as the main threats to the snow leopard. Standardized sign surveys, preferably supplemented by sampling with remote cameras or with genetic analysis of scats would provide robust baseline information on the abundance of snow leopards in this conservation area.